THE CONVENIENCE TO ESTABLISH OF THE JURY SYSTEM IN CRIMINAL JUSTICE OF HISPANIC AMERICANS PERIPHERAL COUNTRIES - Ríos Patio, Gino (2017)
This article starts with the precarious index of credibility and the high level of corruption shown by the administration of justice in Peru and the other peripheral  countries  of the region, which undoubtedly constitutes a serious problem of fragility and institutional instability   in   democracy;   situation from which it critically analyzes the advisability of establishment of the criminal justice system by means of a jury in the peripheral countries, in order to guarantee its effective functioning and to end the current system of tried justice that is unsuccessful to contribute to the maintenance of social peace, because of its biased, highly selective, hatefully discriminating and reproductive character of violence, with the aggravating factor that has as its author the State. The central objective of the article is to demonstrate the need for a cultural change and awareness of citizenship in the peripheral countries of the region, to move from a sys